Jessore and Tongi: urban livelihoods in the slums (International Food Policy Research Institute, 2003)
In 1997, CARE-Bangladesh undertook a livelihood security assessment of urban slum households in the cities of Tongi, Khulna and Bogra. Based on the findings of that study and a review of secondary literature, the SHAHAR (Supporting Household Activities for Health, Assets and Revenue) project was conceptualized and designed. The project's activities, meant to improve livelihoods of the urban poor included infrastructure improvements, such as community toilets; health, hygiene and nutrition education; provision of credit and vocational training; and community mobilization and institutional strengthening, especially of the local NGOs that implement the project. As part of this USAID-funded project, a baseline survey was conducted in 2000 by CARE and IFPRI in slums and low-income settlements within the municipal areas of Jessore and Tongi.